Evaluation of Drug Treatment Programs at the State Correctional Institution in Chester, Pennsylvania, 2003-2004 - Welsh, Wayne N. ([Verlag nicht ermittelbar], 2007)
The purpose of this project was to evaluate the alcohol and other drug (AOD) treatment programs at a specialized treatment prison, the State Correctional Institution (SCI) at Chester, Pennsylvania. The Chester prison is a 1,215-bed medium security prison for male inmates with a documented history of substance abuse. Programs included an intensive, 12-month therapeutic community (TC) drug treatment for high-need inmates and a 12-month outpatient (OP) program for inmates requiring less intensive treatment. Inmates who met eligibility criteria for the Chester facility were randomly assigned to the TC (n = 347) or OP (n = 384) program. The researchers utilized individual measures and outcome measures in this study.